2018
DOI: 10.21272/mmi.2018.4-17
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in Public Finance Management of Sustainable Human Development

Abstract: It is proved that peculiarities of countries with the social-oriented economy are defined by either sufficient costs for the social sphere maintenance and development, or also by their essential influence on the citizens' welfare, as evidenced by the human development index, which is calculated on the basis of the citizens' material situation indicators and social and demographic indicators. Countries with Scandinavian and Western European social and economic development models are in the category with the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…M. Palienko et al (2017) identified the role of fiscal decentralisation and its impact on macroeconomic stability. L. Kozarezenko et al (2018) analysed the impact of fiscal decentralisation in Ukraine on the development of human capital in territorial communities. T. Vasylieva et al (2018) analysed the arguments and counterarguments within the scientific debate on determining the optimal level of decentralisation that would contribute to the country's innovative development.…”
mentioning
confidence: 99%
“…M. Palienko et al (2017) identified the role of fiscal decentralisation and its impact on macroeconomic stability. L. Kozarezenko et al (2018) analysed the impact of fiscal decentralisation in Ukraine on the development of human capital in territorial communities. T. Vasylieva et al (2018) analysed the arguments and counterarguments within the scientific debate on determining the optimal level of decentralisation that would contribute to the country's innovative development.…”
mentioning
confidence: 99%